POWER/HVMOS Devices Compact Modeling - Grabinski, Wladyslaw; Gneiting, Thomas; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Semiconductor power electronics plays a dominant role due its increased efficiency and high reliability in various domains including the medium and high electrical drives, automotive and aircraft applications, electrical power conversion, etc. Power/HVMOS Devices Compact Modeling will cover very extensive range of topics related to the development and characterization power/high voltage (HV) semiconductor technologies as well as modeling and simulations of the power/HV devices and smart power integrated circuits (ICs). Emphasis is placed on the practical applications of the advanced semiconductor technologies and the device level compact/spice modeling. Power/HVMOS Devices Compact Modeling is intended to provide reference information by selected, leading authorities in their domain of expertise. They are representing both academia and industry. All of them have been chosen because of their intimate knowledge of their subjects as well as their ability to present them in an easily understandable manner.
Keywords: Engineering; Computer simulation; Microwaves; Systems engineering; Optical materials; Engineering; Circuits and Systems; Simulation and Modeling; Optical and Electronic Materials; Microwaves, RF and Optical Engineering